Influence of Maternal Glycemia on Intrauterine Fetal Adiposity Distribution after a Normal Oral Glucose Tolerance Test at 28 Weeks Gestation - Farah, Nadine (Hindawi Publishing Corporation, 2011)
Objective. To examine the relationship between maternal glucose levels and intrauterine fetal adiposity distribution in women with a normal oral glucose tolerance test (OGTT) at 28 weeks gestation. Study Design. We recruited 231 women with a singleton pregnancy. At 28 and 37 weeks gestation, sonographic measurements of fetal body composition were performed. Multiple regression analysis was used to study the influence of different maternal variables on fetal adiposity distribution. Results. Maternal glucose levels correlated with the fetal abdominal subcutaneous tissue measurements (r = 0.2; P = 0.014) and with birth weight (r = 0.1; P = 0.04). Maternal glucose levels did not correlate with the fetal mid-thigh muscle thickness and mid-thigh subcutaneous tissue measurements. Conclusion. We found that in nondiabetic women maternal glucose levels not only influence fetal adiposity and birth weight, but also influence the distribution of fetal adiposity. This supports previous evidence that maternal glycemia is a key determinant of intrauterine fetal programming.